The ebb and flow of consumer identities: the role of memory, emotions and threats. (August 2016) - Reed, Americus; Forehand, Mark R
Highlights: Consumer identities are inherently flexible and dynamic. Identity dynamism is influenced by six processes ranging from adoption to expulsion. These processes are influenced by consumer memory, emotions, and identity threats. Abstract : It is well established that consumers use their product and brand choices to signal and reinforce identities. More recently, consumer researchers have begun to focus on the dynamic nature of identity. Moving beyond the momentary effect of a given identity on behavior, newer research investigates how a constellation of identities influence each other and how this interface drives long-term consumption and behavioral patterns. Of particular interest are the processes by which an identity becomes strengthened and weakened over time — both in isolation and also with respect to other identities the consumer may hold. We review these psychological processes based on recent consumer research in the areas of memory, emotions, and threats to identity.